1986
DOI: 10.1093/auk/103.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Low Genic Variation between Black Ducks and Mallards

Abstract: We used allozyme electrophoresis to estimate the degree of genetic differentiation among allopatric and sympatric populations of American Black Ducks (Anas rubripes) and Mallards (A. platyrhynchos). Mallards were collected in California, Saskatchewan, Manitoba, and Ontario, and Black Ducks were collected in Newfoundland, Nova Scotia, and Ontario. The mean genetic distances, D̄, between Black Duck populations (0.0007), between Mallard populations (0.0010), and between Mallard and Black Duck populations (0.0006)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…Hybridization leading to the transfer of mtDNA from one species to another can result in a mtDNA tree that is incongruent with the species tree, but it will not necessarily prevent species from being distinguished, unless the mitochondrial transfer is so recent that their sequences have not diverged (Moore 1995). However, recent hybridization will lead species to share COI barcodes, and we expect that more intensive study will reveal such shared sequences in species that are known to hybridize, such as the white-headed gulls (Crochet et al 2003) and Mallard/Black Ducks (Ankney et al 1986; Avise et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Hybridization leading to the transfer of mtDNA from one species to another can result in a mtDNA tree that is incongruent with the species tree, but it will not necessarily prevent species from being distinguished, unless the mitochondrial transfer is so recent that their sequences have not diverged (Moore 1995). However, recent hybridization will lead species to share COI barcodes, and we expect that more intensive study will reveal such shared sequences in species that are known to hybridize, such as the white-headed gulls (Crochet et al 2003) and Mallard/Black Ducks (Ankney et al 1986; Avise et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Despite high rates of observed interspecific interactions between black ducks and mallards in the middle part of the 20th century (Ankney et al, 1986;Avise et al, 1990;Heusmann, 1974;Mank et al, 2004;McAuley, Clugston, & Longcore, 1998;Merendino & Ankney, 1994;Merendino, Ankney, & Dennis, 1993), our results do not support the eastern hybrid swarm hypothesis or predict the subsequent genetic extinction of the black duck (Rhymer, 2006). ADMIXTURE analysis of our dataset suggests a minimum ~25% hybridization rate between mallards and black ducks (Table 1), which is substantially higher than rates between mallards and either Mexican ducks (~2%; Lavretsky, Dacosta et al, 2015) or mottled ducks (~5%; Ford, Selman, & Taylor, 2017;Peters et al, 2016 Alternative to assortative mating limiting gene flow, we hypothesize that the possibility to reestablish the parental lineage through backcrossing in only a few generations may be playing an important role in maintaining black ducks in the face of relative high rates of hybridization.…”
Section: Genomics Of Hybridization and Islands Of Differentiationmentioning
confidence: 99%
“…Among the monochromatic species, black ducks have the highest rates of hybridization and introgression with mallards (Lavretsky, Janzen, & McCracken, ), and previous studies have suggested either that the two forms are conspecific (Ankney et al, ), or that black ducks have suffered a complete breakdown of their genetic distinctiveness (Mank, Carlson, & Brittingham, ). Although the frequency of mixed pairs and hybrid individuals remains uncertain (Heusmann, ; Johnsgard, ; Kirby, Reed, Dupuis, Obrecht, & Quist, ), black ducks and mallards are genetically indistinguishable based on allozymes (Ankney et al, ), microsatellites (Mank et al, ), and sequence data from a limited number of mitochondrial and nuclear genes (Johnson & Sorenson, ; Lavretsky, Hernández Baños, & Peters, ; Lavretsky, McCracken, et al, ; McCracken et al, ). ddRAD‐seq methods, however, have provided sufficient genomic coverage and allele frequency differences to identify population structure, hybrid individuals, founder events, and genomic regions putatively under divergent selection between mallards and Mexican ducks (Lavretsky et al, ), between the two mottled duck subspecies (Peters et al, ), and more recently between mallards and black ducks (Lavretsky et al, ).…”
Section: Introductionmentioning
confidence: 99%